Co-occurences of kok and other markers in colloquial Jakartan Indonesian - Rika Mutiara (State institute of islamic studies salatiga, 2019)
This study analyzes discourse marker (DM) kok (why) in colloquial Jakartan Indonesian. Co-occurences of markers are noticeable features. It focuses on examining the emotive and textual functions of the co-occurences of kok and other markers. This study applied corpus methods. It was found that there are 7 markers co-occur with kok namely lho, eh, oh, lha, wah, ah, and ih that always appear on the left side of kok. Only DM sih occurs on the right side. In emotive functions, the co-occurrences were used to show shock, disappointment, and disgust. Three markers might occur together in one utterance which cause more complex senses. Some utterances with kok appear repeatedly in the form of questions. It seems that in questions with kok, the speakers feel more curious and demand more responses. In textual functions, the speakers use the co-occurrences to raise a topic, emphasize, demand answers, and negotiate. Moreover, it was also used when the speakers have just noticed something and tried to make the interlocutors notice.